2021
DOI: 10.1186/s12879-021-05787-4
|View full text |Cite
|
Sign up to set email alerts
|

Consistent use of lipid lowering therapy in HIV infection is associated with low mortality

Abstract: Background In people living with HIV (PLWH), statins may be disproportionately effective but remain underutilized. A large prospective trial in patients with low to moderate cardiovascular (ASCVD) risk will reveal whether they should be considered in all PLWH. But its effect size may not apply to real-world PLWH with higher ASCVD and mortality risk. Also, the clinical role of non-statin lipid-lowering therapy (LLT) and LLT adherence in this population is unknown. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Registry data of PLWH within the U.S. Veterans Affairs system notes a 52% mortality reduction among PLWH with consistent statin use. 24 Additionally, lack of randomized, controlled trials within this patient population led to the currently ongoing trial of pitavastatin, known as the REPRIEVE (Randomized Trial to Prevent Vascular Events in HIV) trial. 25 The REPRIEVE trial will be the first to specifically evaluate major adverse cardiovascular events (MACE) in over 7,500 primary prevention PLWH initiated on a moderate-intensity statin or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Registry data of PLWH within the U.S. Veterans Affairs system notes a 52% mortality reduction among PLWH with consistent statin use. 24 Additionally, lack of randomized, controlled trials within this patient population led to the currently ongoing trial of pitavastatin, known as the REPRIEVE (Randomized Trial to Prevent Vascular Events in HIV) trial. 25 The REPRIEVE trial will be the first to specifically evaluate major adverse cardiovascular events (MACE) in over 7,500 primary prevention PLWH initiated on a moderate-intensity statin or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis by excluding one study at a time showed consistent results (RR: 0.98 to 1.25, p > 0.05). However, a meta-analysis of the four studies (23,25,30,31) showed that statin use was significantly related to a reduced risk of cancer in PLWH (RR: 0.73, 95% CI: 0.58 to 0.93, p = 0.009, I 2 = 49%; Figure 2C). Sensitivity analyses by excluding one study at a time also showed consistent results (RR: 0.64 to 0.78, p < 0.05).…”
Section: Association Between Statin Use and Risks Of Cardiovascular Events And Cancer In People Living With Hivmentioning
confidence: 99%
“…It was shown that a total of 5,320 studies were obtained after literature search in the Medline, the Embase, and the Web of Science databases after excluding of the duplicated records, while 504 of them were excluded based on the titles and abstracts primarily because they were irrelevant studies. Then, 16 of the 28 potentially relevant studies were further excluded based on full-text review according to the reasons listed in Figure 1 and the other 12 studies were finally included (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations